Pengaruh Pelatihan Dengan Metode Pbl Terhadap Keterampilan Kader Dalam SDIDTK - Galuh Tunggal Prastiti; Siti Maimunah; Siswanto Pabidang (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Background: Detection and Intervention Program (SDIDTK) is a revision of the EarlyDetection of Growth and Development (DDTK) program which has been carried outsince 1988 and is one of the main programs of the Puskesmas. Based on a reportfrom the Ministry of Health of the Republic of Indonesia, the coverage of Toddler healthservices in early detection of toddler growth and development is 78.11% 10.Monitoring and detection of early childhood growth and development is part of theduties of posyandu cadres in their respective working areas. The task of cadres is very important and complex because the problem of child growth and development is notonly directed at physical growth and development, but also the psychologicaldevelopment of children under five. Harisman, stated that the lack of training andcoaching to improve adequate skills for cadres caused a lack of understanding ofcadres' duties. Early detection education efforts must be increased and one way isthrough training.Method: With pre-experimental design with non-standardized control group pretestdesign on 80 trainees.Results: skill changes in the treatment group MD = -13.07, and control group MD = -9.71. The effect of training on skills F = 12,867 sig 0.001 means there is influence.Conclusion: Training with problem-based learning methods is significantly moreeffective than conventional groups to improve the skills of posyandu cadres inSDIDTK.Keywords: Skills, SDIDTK, PBL